Measuring the independence of aircraft accident investigation authorities in ICAO Member States - Alsrisari, Sami Mohammed (Cranfield University, 2013)
This project examines the safety management of civil aircraft accident investigation authorities in International Civil Aviation Organization (ICAO) Member States, with particular emphasis on the independence of the investigations. The research aims to establish the current level of resources and methodology adopted by Member States’ accident investigation authorities. The output of this work not only identifies the current situation but informs initiatives for some of the States in the process of establishing their investigation capability. ICAO Annex 13 was analysed and found to be based on the principle of independent accident investigations. Also, a four dimensional measuring index (4DMI) has been developed to measure the independence of accident investigations in ICAO Member States. Data were collected from 45 States and are presented in the thesis. As a result of applying the 4DMI to the collected data, the States were ranked according to their scores, and divided into four categories of independence. Analysis of the four categories and the scores from the four dimensions revealed that States approach the concept of investigation independence in different ways; however, there are several practices that are common within the highest independence category and several other practices that are common within the lowest independence category. The research recommends that States should work towards improving their overall investigation independence by implementing the seven identified practices in the High-Independence category and distance themselves from the five practices identified as common in the Low-Independence category.
Keywords: Aviation Safety; 4DMI; Measuring Index; Criminalisation; Investigation Authority; Just Culture; ICAO Annex 13; ICAO USOAP; Accident Investigation